Engagement of Interest-Holders in Evidence Synthesis and Health Guideline Development - Magwood, Olivia Paige (Université d'Ottawa / University of Ottawa, 2024)
Evidence syntheses and guidelines are crucial in evidence ecosystems. These ecosystems ensure that relevant and timely evidence is fit-for-purpose and utilized for health decision-making by interest-holders such as patients, providers and policymakers. Presently, there is a lack of guidance on how to meaningfully engage interest-holders in evidence synthesis and guideline development. The MuSE Consortium aims to address this gap by developing equity-oriented guidance for engagement in these processes. This thesis, part of the MuSE Consortium's research program, addresses knowledge gaps related to equity, barriers and facilitators, and principles and strategies for engagement of interest-holders in evidence synthesis and guideline development. We conducted a scoping review of evidence synthesis literature, identifying considerations for engagement across equity characteristics and summarizing principles to support equitable engagement. Additionally, our qualitative evidence synthesis examined barriers and facilitators to engagement in health guideline development, mapping findings to the GIN-McMaster Checklist for Guideline Development. We also interviewed 43 interest-holders to identify principles and strategies to promote their engagement in the guideline development process. Our scoping review revealed that engagement in evidence synthesis is concentrated in high-income English-speaking countries, with technology access issues leading to resource bias and exclusion of people from lower socio-economic positions. We identified four principles for equitable engagement: addressing power dynamics, ensuring accessibility, promoting diversity and inclusion, and ethical considerations. Our qualitative evidence synthesis identified 24 barriers and 28 facilitators for engagement in health guideline development. Key facilitators included implementing an organizational engagement model, recruiting knowledgeable and diverse interest-holders, defining clear roles and responsibilities, providing training and support, and addressing power dynamics. Interviews with stakeholders underscored the importance of horizontal power structures and shared decision-making. Participants emphasized the need for epistemic justice, promoting fairness and equality in knowledge production. Strategies included engaging interest-holders in governance, setting clear expectations and timelines, fair compensation, and meaningful engagement throughout the process. These findings are widely applicable to any organization or government producing evidence syntheses, health recommendations, or guidelines. Equitable engagement ensures that all voices are heard and valued in decision-making processes, addressing power imbalances and social inequities, and leading to more effective health interventions and outcomes.
Keywords: Interest-holders; Stakeholder engagement; Patient and public involvement; Evidence synthesis; Clinical practice guideline; Barriers and facilitators; Health equity